PENGOLAHAN SAMPAH 3R DAN PEMBUATAN EKOENZIM PADA KELOMPOK TANI KEDUNGMULYO, DESA KEDUNGJATI, KECAMATAN BALEREJO, KABUPATEN MADIUN - Nurharibnu Wibisono; Sulistya Eviningrum; Handaru Agnyana (Universitas Merdeka Madiun, 2024)
The waste problem will become a major problem for humans and the environment if not handled properly. Some people still do not understand the importance of waste sorting with the 3R concept. The community's dependence on chemical fertilizers needs to be given an alternative replacement through the manufacture of organic fertilizers. The method of implementing this community service is counseling and training. In the counseling session, material was given on environmental conservation with the 3R concept (reduce, reuse, recycle). In the second session, material was given on how to make eco-enzymes from fruit waste. Participants in the counseling and training were the Kedungmulyo Farmers Group, Kedungjati Village, Balerejo District, Madiun Regency. Ecoenzymes are useful for liquid plant fertilizers and can be sprayed on plants, pest repellents, a mixture of washing soap and floor cleaners, and river water cleaners. Participants can understand the material on environmental conservation through waste sorting with the 3R concept (reuse, reduce, recycle). Participants can understand and practice making eco-enzymes. The method of making ecoenzyme is to put in leftover fruit and/or vegetables plus white sugar/brown sugar (molasses)/cane molasses plus water, ratio 3:1:10. Next, the mixture of ingredients is put into a bottle/gallon, given an exhaust air channel through a small hose. The end of the hose is put in water in a small bottle to make it sterile. The ecoenzyme fermentation process lasts for 3 months.